Bromeliads as biodiversity amplifiers and habitat segregation of spider communities in a Neotropical rainforest - Gonçalves-Souza, Thiago [UNESP] (2010)
Although bromeliads can be important in the organization of invertebrate communities in Neotropical forests, few studies support this assumption. Bromeliads possess a three-dimensional architecture and rosette grouped leaves that provide associated animals with a good place for foraging, reproduction and egg laying, as well as shelter against desiccation and natural enemies. We collected spiders from an area of the Atlantic Rainforest, southeastern Brazil, through manual inspection in bromeliads, beating trays in herbaceousshrubby vegetation and pitfall traps in the soil, to test if: 1) species subsets that make up the Neotropical forest spider community are compartmentalized into different habitat types (i.e., bromeliads, vegetation and ground), and 2) bromeliads are important elements that structure spider communities because they generate different patterns of abundance distributions and species composition, and thus amplify spider beta diversity. Subsets of spider species were compartmentalized into three habitat types. The presence of bromeliads represented 41 of the increase in total spider richness, and contributed most to explaining the high beta diversity values among habitats. Patterns of abundance distribution of the spider community differed among habitats. These results indicate that bromeliads are key elements in structuring the spider community and highlight the importance of Bromeliaceae as biodiversity amplifiers in Neotropical ecosystems. © 2010 The American Arachnological Society.